Metal–Phenolic Carbon Nanocomposites for Robust and Flexible Energy‐Storage Devices. Issue 8 (11th April 2017) - Oh, Jun Young; Jung, Yeonsu; Cho, Young Shik; Choi, Jaeyoo; Youk, Ji Ho; Fechler, Nina; Yang, Seung Jae; Park, Chong Rae
Abstract: Invited for this month′s cover is the group of Chong Rae Park at Seoul National University. The image shows that metal– phenolic network on carbon nanotubes can provide unique capacitive performances and mechanical properties for supercapacitor electrodes. The Full Paper itself is available at 10.1002/cssc.201601615 . Abstract : "This newly designed supercapacitor electrode will open a platform toward the development of flexible energy storage devices…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201601615 . View the Front Cover here:10.1002/cssc.201700550 .